Conversation questions for Professors Anne Simon and Stephanie Posthumus. Issue 1 (1st January 2021) - Hollister, Lucas; Posthumus, Stephanie; Simon, Anne
Abstract: These conversations highlight the ways in which Stéphanie Posthumus and Anne Simon, who work in different academic fields but often look at similar literary texts written in French, envision ecocriticism and zoopoetics. Drawing on their research of the last twenty years, they discuss intersections and differences of these two approaches within their respective geographical contexts, North American and European (and more specifically French). They locate ecocriticism and zoopoetics in the complex and plural histories of their emergence and development while also making comparisons with similar fields such as geopoetics and environmental humanities. They foreground key objectives such as decentering the human and grounding language in the body, advocating for subjects deemed "unsuitable, " bringing together literature, ecologies and animal space-time, examining their objects of study from the perspective of the text's individual stylistic innovations, reconfiguring literary canons and literary histories, and inventing new narratives and explorations around terms such as oikos, machines, arche …) Examining notions like identity, limits and interstices, they underscore the political and ethical dimensions of ecocritical or zoopoetic literature. Finally, they affirm the ever-changing frontiers and constantly evolving perspectives of their two fields.